A CFD Study of Vortex-Induced Motions of a Semi-Submersible Floating Offshore Wind Turbine - Yuanchuan Liu; Dunjie Ge; Xinglan Bai; Liang Li (Energies, 2023)
Vortex-induced motion (VIM) is a critical issue for floating structures made of one or more columns, due to its significant impacts on their operational stability. Supported by column-type floating platforms, floating offshore wind turbines (FOWTs) may also experience large-amplitude VIM responses in current flow. Existing research on FOWTs has mostly focused on their wind/wave induced responses, yet less attention has been paid to their responses in current flow. In this paper, the VIM of the OC4 semi-submersible FOWT platform is studied numerically over a wide range of flow velocity. Three incidence angles, i.e., 0°, 90°, and 180°, are considered and the effect of current incidence on platform VIM is analysed. Results show that the so-called lock-in phenomenon is present and that a large transverse response amplitude of more than 0.3D persists until Vr = 30, with its maximum reaching over 0.8D at Vr = 8. Meanwhile, the transverse response amplitude for cases with the incidence angle of 180° is generally smaller, with a narrower lock-in regime, than those under the other two incidence scenarios. Flow field visualisation reveals that upstream vortices continuously interact with the downstream side column when the incidence angle turns to 180°, impacting the vortex shedding process and consequently fluid forces of the downstream column.